Sistema informático para analítica de datos con Python para la proyección de las redes de distribución de Electro Oriente S.A. 2024 - Vela Lomas, Walner Rafael (2025)
Population growth implies the appearance of new human settlements and consequently, for Electro Oriente (ELOR), the need to provide electrical services appears. ELOR senior management is urged to have the estimation of the electrical network for decision making, to prevent and address the needs that arise in these areas within the province of Maynas. In this sense, the objective is to determine if the computer system for data analysis using Python allows to project the expansion of ELOR networks in terms of cable length, power and costs 2024; it is expected that the implementation will achieve the projection, this implies finding the equations of the curve that best fits the dispersion of points in the Cartesian plane. The research is applied, longitudinal and retrospective. The ELOR database will be used from 1970 to 2024. The chronological series design is used to evaluate the evolution of the electrical network as a function of time. The equations as a function of time are: for the cable length = 9,627 ∗10−1420,165, for the power = 330,307−639617,726 ⁄ and for the cost = 2,012 ∗10−640,082, each with a high correlation coefficient. With a significance level of 5%, it is concluded that the IT solution, with data analytics, will allow to project the expansion of the ELOR networks in terms of cable length, power and cost 2024.